ATTRACTING FOREIGN DIRECT INVESTMENT FOR DEVELOPMENTECO-INDUSTRIAL PARK MODEL IN THE RED RIVER DELTA - Ngoc Tru, Pham (Tạp chí Khoa học Trường Đại học Sư phạm Hà Nội: Khoa học Xã hội, 2025)
This research proposes strategic solutions for attracting Foreign Direct Investment (FDI) to develop eco-industrial parks in the Red River Delta region through 2030, with a vision for 2050. The author’s proposed solutions are grounded in a comprehensive analysis of the current status and developmental trends of eco-industrial park models, forecasted impacts of international and domestic contexts on FDI flows, and the competitive advantages of the Red River Delta region in attracting FDI specifically for eco-industrial parks. Regarding the development plan, the research focuses on proposing spatial distribution strategies across two sub-regions, the optimal number of industrial parks, and parks as well as the orientation to attract key industries in eco-industrial parks. To enhance FDI attraction effectiveness for eco-industrial park development, the author proposes concentrated implementation of solutions in three critical areas: infrastructure modernization, specialized development support policies, and regional linkages in promoting foreign direct investment.